EFEKTIFITAS EKSTRAK DAUN PANDAN WANGI DALAM PENGENDALIAN LALAT RUMAH DI WORKSHOP POLTEKKES KEMENKES BENGKULU - Haidina Ali; Desti Dwi Cahyani (Poltekkes Kemenkes Jambi, 2016)
House fly is one disturbing insects and insect-borne diseases as well as on human health thatcan spread the disease cholera, typhoid and dysentery and other stomach ailments. Efforts to control anderadicate the disease vector needs to be done to prevent disease transmission. One such effort is to useplant-based insecticides. The purpose of this study was to determine the effectiveness of fragrant pandanleaf extract as an effort to control houseflies.Quasi-experimental type of research is to use the approach of Post Test Only With Control GroupDesign. Object of this research is the house fly's in the TPS Polytechnic Kemenkes Bengkulu, a sample of600 flies. Method of collecting data by counting the number of dead flies in a cage after being giventreatment. Data analysis is performed with univariate and bivariate analysis using one way ANOVAstatistical test.The results using fragrant pandan leaf extract at a dose of 10%, 20% and 30% were able to kill afly with an average of 8 individuals (16.7%), 17 individuals (34.7%), 21 individuals (42%) and results of thestatistical test known one way ANOVA p value = 0.000 <0.05. It means that there are differences in thenumber of deaths flies home with various dose administration fragrant pandan leaf extract in killing houseflies.Study is expected to be an alternative in handling house flies.